Validitas Media Interaktif Berbasis Genially Menggunakan Problem Based Learning Pada Pembelajaran Pendidikan Pancasila di Sekolah Dasar - Reinita; Siti Nurhasanah (SAFE-Network, 2025)
Pancasila Education learning plays an important role in shaping students' character. However, in practice, students are less enthusiastic in participating in learning due to the use of learning media that tends to be conventional and does not involve students in the learning process. Therefore, this study aims to develop and test the validity of Genially-based interactive learning media in Pancasila Education subjects in Elementary Schools. Media validity is assessed based on aspects of content suitability, language suitability and media display carried out by material experts, media experts and language experts. The research method used is Research and Development (R&D) development research with the ADDIE development model which at this stage focuses on product validation. The data collection instrument is a validation sheet given to experts. The validation results show that Genially-based interactive learning media obtained the